Clinicopathological study of cardiac tamponade due to pericardial metastasis originating from gastric cancer - Kobayashi, Michiya (World J Gastroenterol, 2005)
AIM: To review the cases reported in the literature, examined their clinicopathological features, and evaluated the efficacy of different therapeutic modalities for this rare condition. METHODS: A search of the MEDLINE database revealed 16 cases of pericarditis carcinomatosa (PC) originating from GC reported in the literature between 1982 and 2005. Additional detailed data were obtained from the authors of these studies for subsequent clinicopathological investigation. We have also described about a case study from our own clinic. RESULTS: The mean age of cases with pericarditis carcinomatosa originating from GC was 54 years. Females were diagnosed at a younger age (46.3 years) compared to males (58 years). The mean survival period after diagnosis was 4.5 mo. No statistical differences in the length of survival time were found between different therapeutic modalities, such as drainage, and local and/or systemic chemotherapy after drainage. However, three cases who underwent systemic chemotherapy survived for more than 10 mo. Cases that developed metachronous cardiac tamponade for more than 2 years after the diagnosis of GC generally survived for a longer period of time, although this was not statistically significant. Multivariate analysis revealed that low levels of carcinoembryonic antigen (CEA), and CEA and/or cancer antigen 19-9 (CA 19-9) were associated with longer survival. CONCLUSION: Cases with low levels of CEA, and CEA and/or CA 19-9 should undergo systemic chemotherapy with or without local chemotherapy after drainage.